Auteurs des articles et des recensions (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Auteurs des ouvrages recensés (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Bibliographie sommaire du rapport Woods (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index alphabétique (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index alphabétique : Les relations du travail au Canada (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index méthodique (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index méthodique des ouvrages recensés (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Index méthodique des titres (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La responsabilité civile des centrales syndicales – Jugements de la Cour Suprême du Canada dans la cause Gaspé Copper Mines vs United Steel Workers of America (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Liste des descripteurs génériques (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Livres reçus (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Publications récentes (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Références bibliographiques (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The duty of fair representation – effective protection for individual rights in collective agreements? - Adell, B. L. (Relations industrielles / Industrial Relations, 1970)
The author uses the example of Fisher against Pemberton to illustrate the case of an individual employee action against his union for breach of the union*s duty of fair representation.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Study of Recruitment Methods in Canada’s Largest Industrial Concerns - Alpander, Guvenc G. (Relations industrielles / Industrial Relations, 1970)
The author studies the recruiting methods practiced nowadays in the larger firms of Canada. He makes recommendations of eliminating situations which could minimize or even impeach the due process of these methods.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

High Wages Policy - Beach, Carl F. (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor Relations and the Law in Belgium and the United States - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1970)
This article reviews "Labor Relations and the Law in Belgium and the United States" by Shaw Fairweather et al.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le perfectionnement des cadres dirigeants et les politiques et pratiques en matière d’administration du personnel en Asie - Beaulieu, Jean-Pierre (Relations industrielles / Industrial Relations, 1970)
This article reviews "Le perfectionnement des cadres dirigeants et les politiques et pratiques en matière d’administration du personnel en Asie" from le Bureau interationale du travail (Genève).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Cost-Benefit Analysis of Manpower Policies - Bélanger, Gérard (Relations industrielles / Industrial Relations, 1970)
This article reviews "Cost-Benefit Analysis of Manpower Policies" by G.G. Somers and edited by W.D. Wood.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Plein emploi, stabilité des prix, négociation collective et le rapport Woods - Bélanger, Gérard (Relations industrielles / Industrial Relations, 1970)
L'auteur critique la troisième partie du rapport sur Les relations du travail au Canada. Deux problèmes y sont étudiés: la compatibilité des objectifs de plein emploi et de stabilité des prix et les relations entre la convention collective et ces objectifs.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

An Occupation in Conflict : A Study of the Personnel Manager - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1970)
This article reviews "An Occupation in Conflict : A Study of the Personnel Manager" by George Ritzer and Harrison Trice.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Automation: Threat of Promise? – Impact and Implications in Australia - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1970)
This article reviews "Automation: Threat of Promise? – Impact and Implications in Australia" edited by G.W. Ford.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Développement organisationnel : évaluation d’un programme en cours - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1970)
L'intervention sur les organisations est une activité qui utilise largement des concepts et des modes de raisonnement propres aux sciences du comportement. Elle constitue une forme de consultation qui diffère sensiblement de celle qui se réfère aux « classiques » en administration et aux méthodes de la recherche opérationnelle. Chaque intervention s'insère dans une séquence pour constituer un programme intégré de développement organisationnel. L'auteur de cet article présente le modèle de développement utilisé par le Centre de formation et de consultation (CDE) et donne un compte-rendu des résultats obtenus à ce four dans une entreprise québécoise 1. 1 Nous tenons à remercier Messieurs Raymond Tremblay et Guy Darveau du Centre de formation et de consultation pour avoir revisé la partie théorique de ce texte et la direction de l'entreprise Groupe Commerce pour avoir répondu aux questions posées.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Personnel Management : Theory and Practice - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1970)
This article reviews "Personnel Management : Theory and Practice" by Dalton E. McPharland.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Pourquoi et comment déléguer - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1970)
This article reviews "Pourquoi et comment déléguer" by Roland Claude.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Work in Traditional and Modern Society - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1970)
This article reviews "Work in Traditional and Modern Society" by Stanley H. Udy, Jr.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Comment rédiger vos rapports - Bernier, Jean (Relations industrielles / Industrial Relations, 1970)
This article reviews "Comment rédiger vos rapports" by Georges Bousquie.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor Relations and Collective Bargaining, Text and Case - Bernier, Jean (Relations industrielles / Industrial Relations, 1970)
This article reviews "Labor Relations and Collective Bargaining, Text and Case" by Max G. Wortman Jr. and George C. Witteried.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Technology and Unemployment : A Comparative Study - Blum, Albert A. (Relations industrielles / Industrial Relations, 1970)
In this paper, the author summarizes how countries try to prevent job losses caused by technological change and how they assist workers who are discharged as a result of new machines.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le rapport Woods et le rapport Donovan - Bonenfant, Jean-Charles (Relations industrielles / Industrial Relations, 1970)
A l'occasion de la publication du rapport Woods, l'article rappelle que quelques mois auparavant, en Grande-Bretagne une commission royale, la Commission Donovan, a rendu public un rapport analogue sur les relations du travail. Dans une seconde partie, le problème même des enquêtes est étudié pour en apprécier les inconvénients et les avantages.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Canadian Labour Economics - Brody, Bernard (Relations industrielles / Industrial Relations, 1970)
This article reviews "Canadian Labour Economics" by Stephen G. Peitchinis.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Must an individual union member’s rights be sacrificed to protect the group interest? - Bromstein, Reuben M. (Relations industrielles / Industrial Relations, 1970)
Assuming that an individual employee can neither sue directly on the collective agreement nor force the union to take his case through to arbitration, can he proceed against the union for its failure to discharge its duty to represent his interests?
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le bilan de l’année 1969 en droit du travail français - Camerlynck, G. H. (Relations industrielles / Industrial Relations, 1970)
Cette nouvelle chronique, qu'assure le professeur G.H. Camerlynck, de la Faculté de droit et des sciences économiques de Paris, permettra au lecteur de faire le point de révolution annuelle du droit du travail français. Ce système et l'aménagement juridique nord-américain des relations du travail, au départ si différents, commenceraient-ils à converger à certains égards ? Acceptation, maintenant, par le premier, d'une présence syndicale dans l'entreprise ; tendance plus accentuée, pour ce qui est du second, notamment au Québec, à la négociation par grands secteurs...
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Leadership Styles for Foreign Operations - Carlisle, Arthur Elliott (Relations industrielles / Industrial Relations, 1970)
The author discusses on the criteria to follow in choosing a style of leadership which is to be applied to foreign operations. In a country which is colonial in tradition, the authoritarian job-centered approach may be preferable. On the long run nonetheless, an organization wishing to be accepted in a foreign country can benefit enormously by using a democratic people-centered style in managerial decision making.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Négociation locale et négociation sectorielle - Cinq-Mars, Normand (Relations industrielles / Industrial Relations, 1970)
A partir des limitations de notre régime de négociation collective, l'auteur tente d'élaborer, à laide de certains critères, de nouvelles structures de négociation.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Collective Bargaining Process - Craig, Alton W.J. (Relations industrielles / Industrial Relations, 1970)
This paper attempts to highlight the parts of the Woods 1 Report dealing with the collective bargaining process. The author discusses how the goals (inputs) of labour and management are converted to outputs via the mechanisms of collective bargaining, and gives his personal opinions on the positions advanced in the Task Force Report. 1. Canadian Industrial Relations, The Report of the Task Force on Labour Relations, Ottawa, the Queen's Printer, 1969. This document will be referred to throughout this paper as the Task Force Report.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Conciliation : The End of Compulsory Boards - Cunningham, William B. (Relations industrielles / Industrial Relations, 1970)
The Woods' Report has recommended the abolition of compulsory conciliation boards. The recent de-emphasis on compulsory conciliation boards in the provinces of Nova Scotia, New Brunswick and Ontario by legislative changes and administrative practices has led to certain conclusions. Experience has shown that the benefits to collective bargaining have been desirable, and that the incidence and/or magnitude of strikes has not increased.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le Bill 36 et le syndicalisme de cadre - D’Aoust, Claude (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Chômage, inflation et logique syndicale - Dehem, Roger (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Unemployment, Cost and Availability of Accommodation and Wage Changes in Ontario - Della Valle, P. A.; Green, R. (Relations industrielles / Industrial Relations, 1970)
The purpose of this paper is to determine whether there are consistent and significant relationships between wages changes, unemployment and cost and availability of accommodation in urban areas in Ontario.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Avant-propos - Dion, Gérard (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Bibliographie des relations du travail au Canada (1940-1967) - Dion, Gérard (Relations industrielles / Industrial Relations, 1970)
This article reviews "Bibliographie des relations du travail au Canada (1940-1967)" by Louis-Marie Tremblay.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labor and the American Community - Dion, Gérard (Relations industrielles / Industrial Relations, 1970)
This article reviews "Labor and the American Community" by Dereck C. Bock and John Dunlop.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le Mouvement coopératif du Québec et l’éducation des adultes - Dion, Gérard (Relations industrielles / Industrial Relations, 1970)
This article reviews "Le Mouvement coopératif du Québec et l’éducation des adultes" from les cahiers de l’ICEA, no. 10-11.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le Mouvement syndical en Belgique - Dion, Gérard (Relations industrielles / Industrial Relations, 1970)
This article reviews "Le Mouvement syndical en Belgique" by Guy Spitaels.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Psychologie du groupe - Dion, Gérard (Relations industrielles / Industrial Relations, 1970)
This article reviews "Psychologie du groupe" par M.A. Robert.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Présentation = Foreword - Editorial Committee (Relations industrielles / Industrial Relations, 1970)
In 1966, the Prime Minister of Canada, Mr Lester B. Pearson, established a Task Force on Labour Relations composed of H.D. Woods, chairman, from McGill University, A.W.R. Carrothers, from the University of Western Ontario, John G. Crispo, from Toronto University and Gérard Dion, from Laval University. According to the terms of référence, "the Task Force has been set up to examine industrial relations in Canada and to make recommendations to the Government with respect to public policy and labour législation and on such other matters as it considers relevant to the public interest in industrial relations in Canada". On December 31, the Task Force transmitted its Report to the Prime Minister and it was published in March 1969 under the title Canadian Industrial Relations. Relations industrielles-Industrial Relations already published a summary of the Woods' Report and a commentary from professor Adolf Sturmthal. Given the importance of this Report and its possible repercussions upon the whole Canadian industrial relations System, we decided to dedicate a special issue of our Journal to it. Our objective, nevertheless, has not been to consider ail the aspects of the problem raised nor ail the recommendations which were made. We rather wanted to présent a set of opinions and to furnish an instrument which will facilitate further research. We are thus publishing some of the papers presented at the last annual meeting of the Canadian Industrial Relations Research Institute and some other articles. In order to facilitate consultation of the Woods Report, we are also including a topical index of Canadian Industrial Relations and a bibliography of the reactions to the Report. As the Task Force commissionned a series of studies which could prove extremely useful to those in this and related disciplines, we are listing the studies which presently are or will be avaïlable in the near future.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les lendemains de l’arrêt Port Arthur Shipbuilding - Gagnon, Robert; Verge, Pierre (Relations industrielles / Industrial Relations, 1970)
Quelle a été l'attitude des arbitres depuis cet arrêt de la Cour suprême 1 relatif à leurs pouvoirs en matière de contrôle de la sanction disciplinaire imposée par l'employeur ? L'ambivalence de leurs réactions pose à nouveau le problème de la portée véritable de cet arrêt.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Union Mergers - Graham, Harry (Relations industrielles / Industrial Relations, 1970)
The author stresses the importance of reexamining the structure of the American labor movement, which has to face changing economic and social conditions, and depicts the main difficulties which hinder changes in the actual system. His line of study bears specifically on the possibility of union mergers, which seems to be the most practical solution to the present structural inadequacies in unionism.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Theory of Collective Bargaining - Hameed, Syed M.A. (Relations industrielles / Industrial Relations, 1970)
The author brings out the inadequacies of the present theoretical models in explaining collective bargaining and provides the constructs of a more complete and integrated body of theory. He also notes the importance of using functional terms in a theoretical model of this kind.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Participation Achievement and Involvement on the Job - Jacques, Lola (Relations industrielles / Industrial Relations, 1970)
This article reviews "Participation Achievement and Involvement on the Job" by Martin Patchen.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Technological Change & Human Development - Jacques, Lola (Relations industrielles / Industrial Relations, 1970)
This article reviews "Technological Change & Human Development" by Wayne L. Hodges and Matthew A Relly.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

This Third Wage-Labour Unrest and Industrial Conflict in Canada : 1900-1967 - Jamieson, Stuart Marshall (Relations industrielles / Industrial Relations, 1970)
The author investigates the strikes and labour unrest, and the associated widespread violence and illegality in the mid-sixties ; is this a new trend on the Canadian industrial relations scene? It is seen as the crest of the third wave of Canadian labour unrest since 1900. The author supports the main recommendations in the Woods' Report that directly concern the question of labour unrest and industrial conflict.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Les rapports industriels en Yougoslavie - Kostic, Cvetko (Relations industrielles / Industrial Relations, 1970)
Après avoir analysé la structure formelle et la compétence des organes de l'autogestion ouvrière dans l'industrie yougoslave, l'auteur expose les résultats des deux recherches empiriques sur les attitudes et opinions des ouvriers concernant l'autogestion, l'influence de divers organes de l'autogestion, le rôle du parti et des syndicats et la sécurité des ouvriers au travail.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labour Relations and Court Review - L’Heureux, Nicole (Relations industrielles / Industrial Relations, 1970)
This article reviews "Labour Relations and Court Review" by Philip Cutler.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Relations humaines et relations industrielles - Langevin, Jean-Louis (Relations industrielles / Industrial Relations, 1970)
This article reviews "Relations humaines et relations industrielles" by Marcel Bolle De Bal.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Note sur la grève tournante - LeBel, Louis; Verge, Pierre (Relations industrielles / Industrial Relations, 1970)
Une forme nouvelle de grève est apparue au Québec : la« grève tournante », ou arrêt de travail concerté et partiel, exécuté successivement par des ensembles de salariés compris dans une même unité de négociation. Juridiquement, ce procédé doit-il être reçu avec une faveur particulière, en tant qu'instrument de« civilisation » de la grève ? Faut-il, au contraire, y voir une forme particulièrement pernicieuse de l'exercice du droit de grève ?
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Industrialization and the Individual - Mageau, Alfred (Relations industrielles / Industrial Relations, 1970)
This article reviews "Industrialization and the Individual" by James G. London.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

A Critical Appraisal of the Economics Rationale of Government-Subsidized Manpower Training - Mehmet, Ozay (Relations industrielles / Industrial Relations, 1970)
The author endeavors to present a detailed analysis of the economic rationale of a manpower training policy, and provides useful insights on its limits through a selective study of macro-, micro-, and welfare economic theory.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Point de vue d’un économiste sur le rapport de la commission Castonguay-Nepveu sur les professions - Migué, Jean-Luc (Relations industrielles / Industrial Relations, 1970)
Dans un premier temps, l'auteur estime que la démarche de la Commission consistant à faire la classification des occupations par définitions est vide de substance analytique, et donc non susceptible d'aboutir à la compréhension des phénomènes étudiés ni à la formulation de corollaires politiques. Dans un second temps, l'auteur dégage deux principes d'analyse des professions : soit l'absence d'information des consommateurs sur la qualité des services professionnels et l'incitation que subissent les professionnels à se constituer en corporations « fermées » pour promouvoir leurs intérêts.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Task Force Report - Montague, J. T. (Relations industrielles / Industrial Relations, 1970)
The author gives a philosophical analysis of the general tenor of the Woods' Report, and provides a brief appraisal of its observations, particularly in regard to collective bargaining.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’accréditation syndicale au Québec - Morin, Fernand; D’Aoust, Claude; Lachapelle, Raymond (Relations industrielles / Industrial Relations, 1970)
Après avoir rappelé les assises juridiques du régime d'accréditation, l’auteur note les effets de l'accréditation à l'égard de certains salariés dans un premier temps et à l'égard du syndicat dans un second temps.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Aid to the Civil Power: The Canadian Militia in Support of Social Order, 1867–1914 - Morton, Desmond (Canadian Historical Review, 1970)

Les unités de négociation au Québec - Ouellette, Yves; Cardin, Jean-Réal (Relations industrielles / Industrial Relations, 1970)
L'auteur tente de rechercher les éléments fondamentaux d'une notion universelle de fonctionnaire i.e. de rechercher ce qu'il y a de commun dans la plupart des pays dans la nature du rapport entre l'individu fonctionnaire et l’Etat, ce qui permettra de faire la distinction entre le fonctionnaire et le salarié privé et de situer les enseignants et les employés d'hôpitaux par rapport à l'Etat.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Protection of Individual Members of Unions - Palmer, Earl E. (Relations industrielles / Industrial Relations, 1970)
The author discusses the analysis and recommendations jound in the Woods* Report on the position of the individual member of the union. He views the investigation into the rights of individuals in two parts: (1) the extent to which unions are granted exclusive control over employment conditions and (2) the extent to which the services provided by such unions are vital to Us members. Solutions to the problems inherent in individual member versus union conflicts cannot be found in appeals to abstract 'democracy', internal reform or changes in the common law, but through legislation.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Le tribunal du travail - Rousseau, André (Relations industrielles / Industrial Relations, 1970)
L'auteur étudie les dispositions nouvelles relatives au tribunal du travall dans le Code du travail du Québec.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Compulsory Arbitration in Australia - Roy, André (Relations industrielles / Industrial Relations, 1970)
This article reviews the study "Compulsory Arbitration in Australia" by J.E . Isaac.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Professional Workers and Collective Bargaining - Roy, André (Relations industrielles / Industrial Relations, 1970)
This article reviews the study "Professional Workers and Collective Bargaining" by Shirley B. Goldenberg.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Radical Politics and Canadian Labour - Roy, André (Relations industrielles / Industrial Relations, 1970)
This article reviews "Radical Politics and Canadian Labour" by Martin Robin.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Studies in Personnel Psychology/Études en psychologie du travail, Division des méthodes de sélection et du service des tests, Commission de la Fonction Publique du Canada, vol. 1, no 2, oct. 1969, 120 pp. - Royer, Maurice (Relations industrielles / Industrial Relations, 1970)
This article reviews "Studies in Personnel Psychology/Études en psychologie du travail" from the Commission de la Fonction Publique du Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Rythmes de travail… et cadences infernales - Sartin, Pierrette (Relations industrielles / Industrial Relations, 1970)
Dans l'industrie, le problème des rythmes de travail se pose avec acuité. Il est l'un des plus difficiles à résoudre et le chronométrage ne donne que des résultats imparfaits. La nocivité des allures élevées est encore mal connue, mais leur incidence sur la fatigue nerveuse est incontestable. Chacun a un rythme qui lui est propre. Mais ce rythme personnel est « corrigé » par les normes du groupe et par les motivations personnelles. Il faut essayer de se dégager de la notion de rythme maximal pour aller vers celle de rythme optimal qui ménagera à la fois la santé de l'homme, son efficacité, la bonne marche de l'entreprise et l'économie générale.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Industrial Relations in Scandinavia - Schonning, Gil (Relations industrielles / Industrial Relations, 1970)
The author enumerates the characteristics of the Scandinavian system of industrial relations, notes ten of the most significant ones and compares their system with the one prevailing in Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La C.S.N. et la société de consommation - Sexton, Jean (Relations industrielles / Industrial Relations, 1970)
L'auteur présente le modèle de recherche utilisé lors de l'étude sur la Confédération des syndicats nationaux et la société de consommation, expose les difficultés rencontrées lors de la réalisation de ce travail et insiste sur les principales indications que l'on peut en retirer et les hypothèses que l’on est en droit de formuler.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Coalition Bargaining : A Study of Union Tactics and Public Policy - Sichel, Joan (Relations industrielles / Industrial Relations, 1970)
This article reviews the study "Coalition Bargaining : A Study of Union Tactics and Public Policy" by William N. Chernish, number 45 in the series published by the Industrial Research Unit of the University of Pennsylvania.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Cultures in Collision: U.S. Corporate Policy and Canadian Subsidiaries - Sichel, Joan (Relations industrielles / Industrial Relations, 1970)
This article reviews "Cultures in Collision: U.S. Corporate Policy and Canadian Subsidiaries" by Arthur Elliott Carlisle.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Deferment Policy in the Selective - Sichel, Joan (Relations industrielles / Industrial Relations, 1970)
This article reviews "Deferment Policy in the Selective" by David R. Bradford.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Hospital Regulation : The Dilemma of Public Policy - Sichel, Joan (Relations industrielles / Industrial Relations, 1970)
This article reviews "Hospital Regulation: The Dilemma of Public Policy" by Anne R. Somers.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Issues in Indian Labour Policy. Papers and Conclusions of the Fourth National Seminar on Industrial Relations in a Developing Economy - Sichel, Joan (Relations industrielles / Industrial Relations, 1970)
This article reviews "Issues in Indian Labour Policy. Papers and Conclusions of the Fourth National Seminar on Industrial Relations in a Developing Economy" edited by C.K. Johri.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

An Empirical Analysis of Substitution Between Engineers and Technicians in Canada - Skolnik, Michael L. (Relations industrielles / Industrial Relations, 1970)
The author analyzes substitution between engineers and technicians through the application of a derived demand equation model to 1961 Census data and concludes that there is considerable substitution between these groups. The conclusion is qualified by noting certain weaknesses of the data. The results should be viewed in the context of the importance of substitution for manpower and educational planning and the lack of empirical study to date.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Collective Bargaining Results - Smith, Douglas A. (Relations industrielles / Industrial Relations, 1970)
The author of the following article discusses the relationship between inflation and collective bargaining. Collective bargaining cannot in a vacuum create inflationary wage increases. Rather, it is the interaction of mark-up or target-return pricing and profit-based wage demands that sets off the spiral of discretionary increases in wages and prices. In the author's opinion, it would be necessary to strive for intelligent methods of reducing the conflict between good industrial relations and a stable price level or face the consequences of the actions of those who seek to impose un-workable controls on the collective bargaining system.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Conditions de vie et santé des migrants et de leurs familles – Études de médecine sociale - Solasse, Bernard (Relations industrielles / Industrial Relations, 1970)
This article reviews "Conditions de vie et santé des migrants et de leurs familles – Études de médecine sociale" from the Éditions de l’Institut de sociologie (Bruxelles).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’entreprise moderne et le management - Solasse, Bernard (Relations industrielles / Industrial Relations, 1970)
This article reviews "L’entreprise moderne et le management" by Pierre Schil.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’équipement social dans la croissance économique régionale – analyse des méthodes de définition des besoins en équipement sociaux sur le plan régional - Solasse, Bernard (Relations industrielles / Industrial Relations, 1970)
This article reviews "L’équipement social dans la croissance économique régionale – analyse des méthodes de définition des besoins en équipement sociaux sur le plan régional" by Léo H. Klaassen (of l’institut économique néerlandais).
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L’homme et la ville dans le monde actuel - Solasse, Bernard (Relations industrielles / Industrial Relations, 1970)
This article reviews "L’homme et la ville dans le monde actuel" in collaboration with the Centre d’études de la civilisation contemporaine.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La classe ouvrière et le syndicalisme en France 1789-1965 - Solasse, Bernard (Relations industrielles / Industrial Relations, 1970)
This article reviews "La classe ouvrière et le syndicalisme en France 1789-1965" by Georges Vidalenc.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Exceptional Executive, a Psychological Conception - Tremblay, Raymond (Relations industrielles / Industrial Relations, 1970)
This article reviews "The Exceptional Executive, a Psychological Conception" by Harry Levinson.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Jugements récents - Verge, Pierre (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La réintégration forcée du salarié en droit québécois - Verge, Pierre (Relations industrielles / Industrial Relations, 1970)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z